2010
DOI: 10.1038/gt.2010.139
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of MAPK phosphatase-1 local gene transfer in inflammatory bone loss

Abstract: Alveolar bone loss associated with periodontal diseases is the result of osteoclastogenesis induced by bacterial pathogens. The mitogen-activated protein kinase (MAPK) phosphatase 1 (MKP- 1) is a critical negative regulator of immune response as a key phosphatase capable of dephosphorylating activated MAPKs. In this study, rat macrophages transduced with recombinant adenovirus (Ad).MKP-1 specifically dephosphorylated activated MAPKs induced by lipopolysaccharide (LPS) compared with control cells. Bone marrow m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 36 publications
4
74
1
1
Order By: Relevance
“…MKP-1 (gene Dusp1 ), the family archetype, preferentially dephosphorylates phospho (p)-p38 and p-JNK [13]. With regard to oral bone loss, our group has demonstrated that alveolar bone loss is more pronounced in LPS-induced in mice lacking MKP-1 and that overexpression of MKP-1 protects from LPS-induced bone loss [14, 15]. Given the ability of MKP-1 to negatively regulate MAPK induced inflammatory cytokines in response to LPS, we hypothesized that bone loss was due to an exacerbated cytokine response within the periodontal microenvironment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MKP-1 (gene Dusp1 ), the family archetype, preferentially dephosphorylates phospho (p)-p38 and p-JNK [13]. With regard to oral bone loss, our group has demonstrated that alveolar bone loss is more pronounced in LPS-induced in mice lacking MKP-1 and that overexpression of MKP-1 protects from LPS-induced bone loss [14, 15]. Given the ability of MKP-1 to negatively regulate MAPK induced inflammatory cytokines in response to LPS, we hypothesized that bone loss was due to an exacerbated cytokine response within the periodontal microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…While CXCL2 has been shown to be involved in LPS-driven OCgen, the signaling mechanisms governing chemokines in OCgen remain to be defined [19]. In this study, we evaluated the role of MKP-1 in controlling OC-directed bone turnover in response to the periodontal pathogen A. actinomycetemcomitans LPS[15]. As a negative regulator of inflammatory MAPK pathways and subsequent cytokines/chemokines, we hypothesized that MKP-1 may control inflammatory driven OC formation through activity of the chemokine CXCL2.…”
Section: Introductionmentioning
confidence: 99%
“…The Institutional Animal Care and Use Committee at the Medical University of South Carolina approved all experimental protocols. During the last 4 wk of regular chow or HFD feeding, 14 mice (7 fed regular chow and 7 fed a HFD) were injected with LPS (20 µg per mouse) isolated from A. actinomycetemcomitans (strain Y4, serotype B; Yu et al 2011) through both the left and right sides of the palatal gingiva between the maxillary first and second molars, 3 times per week as described previously (Rogers et al 2007;. For control, 14 mice (7 fed regular chow and 7 fed a HFD) were injected with phosphate-buffered saline (PBS), the vehicle for LPS.…”
Section: Animal Treatmentsmentioning
confidence: 99%
“…Systemic transduction with TIMP-4 was reported to reduce both adjuvant-induced arthritis and periodontitis in rats (39). Inhibition of periodontal bone loss following AAV gene transfer of mitogen-activated protein kinase phosphatase-1 (MKP-1), which dephosphorylates MAPKs and inhibits immune responses, was also reported (40). Transduction of gingival tissues with AAV/2/1-tumor necrosis factor receptor-immunoglobulin FIG 6 AAV-sh-Atp6i reduced the expression of osteoclast marker genes and cytokines in periapical lesions.…”
Section: Discussionmentioning
confidence: 99%